A Thiadiazole-Based Covalent Organic Framework: A Metal-Free Electrocatalyst toward Oxygen Evolution Reaction - Mondal, Sujan; Mohanty, Bishnupad; Nurhuda, Maryam; Dalapati, Sasanka; Jana, Rajkumar; Addicoat, Matthew; Datta, Ayan; Jena, Bikash Kumar; Bhaumik, Asim (ACS catalysis, 2020)
Covalent organic frameworks (COFs) have attracted surging interest lately due to their wide potential in several frontline application areas like gas storage, sensing, photovoltaics, fuel cells, active catalyst supports, and so on. However, only very few reports are available for the metal-free electrocatalysis over COFs. Herein, we developed a new thiadiazole-based COF, C4-SHz COF, through the reaction between 1,3,5-tris(4-formylphenyl)benzene and 2,5-dihydrazinyl-1,3,4-thiadiazole that possesses a very high specific surface area of 1224 m2 g–1, unique molecular architecture, high porosity, and abundant active sites. The synthesized C4-SHz COF displayed superior electrocatalytic oxygen evolution reaction (OER) activity and excellent long-term durability. The electrocatalytic performance of the C4-SHz COF achieved a current density of 10 mA/cm2 at an overpotential of 320 mV. The higher activity of the C4-SHz COF could be attributed to the high Brunauer–Emmett–Teller surface area, porosity, and network structure of the π-conjugated organic building blocks, which allowed fast charge and mass transport processes. This work validates the promising potential of a metal-free COF electrocatalyst toward the OER and its capability to replace carbon-based electrocatalysts.